Population Status and Anthropogenic Threats to the African dwarf crocodile (Osteolaemus tetraspis) in the Niger Delta, Nigeria - Efenakpo, Ogaga Dean; Jacob, Daniel Etim; Goodnews, Newson Njoku (Journal of Sustainability and Environmental Management, 2025)
The African dwarf crocodile (Osteolaemus tetraspis), classified as Vulnerable by the IUCN, faces significant threats across its range, yet specific data from many regions, including parts of the Niger Delta, remain scarce. This study aimed to assess the population status, habitat conditions, and anthropogenic pressures impacting O. tetraspis in Omuihechi Community, Aluu, Nigeria. Systematic sampling, involving visual encounter surveys along six established transects, habitat assessments, structured questionnaires, and interviews with local hunters/fishermen (n = 7), was employed. Relative abundance was derived from survey counts, while anthropogenic activities were quantified by frequency of occurrence. The interview data provided valuable insights into hunting pressures and local perceptions. Descriptive statistics were used for data analysis. Farming (19) and logging (7) were the most frequent habitat disturbances. Hunting, primarily for sale (85.71%), has a significant impact on the species, with juveniles being the most targeted size class (57.14%). Relative abundance averaged 102 individuals across surveys, with notable variation between transects (Transect 2 highest: avg. 31; Transect 4 lowest: avg. 9.5). Most hunters (71.43%) caught crocodiles opportunistically, predominantly using wire traps (85.71%) during the dry season (100%). Most respondents (57.14%) perceived a decline in crocodile numbers. O. tetraspis in the Omuihechi Community is under considerable pressure from habitat alteration (primarily farming and logging) and unsustainable hunting practices targeting juveniles. Urgent conservation actions are needed. It is recommended to implement community-based conservation programs focusing on awareness campaigns about the ecological role of crocodiles and the negative impacts of current hunting levels, alongside the development and promotion of alternative livelihood options to reduce reliance on hunting. Enforcement of existing wildlife laws and continued population monitoring are also crucial for the species' long-term survival in the region.